2010
DOI: 10.1016/j.enpol.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease—risk benefits of clean fuel technology and policy: A statistical analysis

Abstract: The hypothesis of this study is that there is a statistical relationship between the cardiovascular disease mortality rate and the intensity of fuel consumption (measured in gallons/square mile) at a particular location. We estimate cross-sectional regressions of the mortality rate due to cardiovascular disease against the intensity of fuel consumption using local data for the entire US, before the US Clean Air Act (CAA) in 1974 and after the most recent policy revisions in 2004. The cardiovascular disease rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Our results confirmed that air pollution has significant adverse impacts on public health, especially in Central/Western China, which accords with many previous studies e.g., [ 1 , 2 , 3 , 11 ]. Past studies mostly examined the potential health effects of air pollution by analyzing average AOI or PM as an independent variable representing air pollution [ 11 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results confirmed that air pollution has significant adverse impacts on public health, especially in Central/Western China, which accords with many previous studies e.g., [ 1 , 2 , 3 , 11 ]. Past studies mostly examined the potential health effects of air pollution by analyzing average AOI or PM as an independent variable representing air pollution [ 11 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…The adverse health effects of air pollution have generated considerable interest, and studies confirm that exposure to air pollution increases health risks, including adverse cardiovascular, respiratory, pulmonary, and other health-related outcomes [ 1 , 2 , 3 ]. The economic and social harms of air pollution arising from its negative effects on public health have been widely discussed, especially in China [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that exposure to air pollution increases more tangible health risks, such as cardiovascular diseases (Gallagher et al 2010), respiratory diseases (Moretti and Neidell 2011; Beatty and Shimshack 2014), hospitalizations (Neidell 2009; Lleras-Muney 2010), and mortality (Jayachandran 2009; Chen et al 2013; Greenstone and Hanna 2014; Tanaka 2015). However, much less is known about how air pollution impairs less tangible outcomes like SWB and mental health, which complement the direct monetary measures of welfare (Graham 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While numerous factors have been recognized in affecting suicidal thoughts and behaviors (STB), such as, life stresses, chronic pain and illness, conflict, disaster, violence, losses, et al [6], the environmental risks have been poorly understood. As a heatedly discussed dimension, air pollution has a detrimental impact on individual health, including higher rates of mortality [11][12][13][14][15], increased incidence of stroke [16], respiratory diseases [17][18][19], and lung and cardiovascular dysfunction [20][21][22][23][24][25][26], to name a few. In fact, air pollution has been revealed to be complicit in over 4 million deaths globally since 2015 [27].…”
Section: Introductionmentioning
confidence: 99%